Assessment of healthcare worker resilience at the epicenter of the 2022 Sudan virus disease outbreak in Uganda: implications for future preparedness - Robert Zavuga; Peter Chris Kawungezi; Brian Agaba; Richard Migisha; Daniel Kadobera; Benon Kwesiga; Paul Edward Okello; Lilian Bulage; Freda Loy Aceng; Emmanuel Batiibwe; Alex Riolexus Ario (BMC Psychology)
Abstract Background Healthcare workers (HCWs) often face mental resilience challenges during public health emergencies, including disease outbreaks. On September 20, 2022, the Uganda Ministry of Health declared an outbreak of Sudan virus disease (SVD). We assessed the level and factors associated with workplace resilience among HCWs working at the epicenter of the SVD outbreak in Mubende and Kassanda districts, Uganda. Methods In March 2023, we conducted a cross-sectional survey among all HCWs (clinical and non-clinical) who served in three facilities directly involved in the SVD response between September 20, 2022─January 23, 2023 (the outbreak period) in Mubende and Kassanda Districts. Risk perception was assessed using 12 statements with a 4-point Likert-type scale. We assessed resilience using the Connor-Davidson Resilience Scale (CD-RISC-10). Resilience was categorized as either resilient or not resilient. Logistic regression was used to identify factors associated with resilience. Results Of 429 eligible HCWs, 400 (93%) participated in the study, and all completed the survey. Mean age was 35 years (range: 20–58); 222 (56%) were male and median work experience was 8 years (range: 1–38). One hundred and ten (28%) were support staff and 72 (18%) were nurses; 344 (86%) worked > 40 h per week. Overall, 23% (95%CI: 9–25%) were resilient. Most participants (89%) reported fear of contracting SVD and concern about workplace stigma if infected. Higher resilience was associated with age > 40 years (adjusted odds ratio [AOR] = 2.1; CI = 1.3–3.5), work experience > 10 years (AOR = 2.2; CI = 1.1–4.7), working > 40 h per week (AOR = 6.8; CI = 2.1–23), and receiving SVD-specific counseling (AOR = 3.3; CI = 1.7–6.5). Conclusion Most HCWs at the SVD outbreak epicenter had low resilience, largely related to fear of infection and stigma. Older age, longer work experience, and access to psychological counselling were associated with higher resilience. Providing targeted mental health support and reducing workplace infection concerns could help strengthen HCW resilience in future outbreaks.